INVESTIGATION ON CONTENT OF FATTY ACIDS, PHOSPHOLIPIDS, AND PHOSPHOLIPID MOLECULAR SPECIES COMPOSITION OF THE VIETNAMESE CORAL Bebryce sp. - Ly, Dang Thi Phuong; Quan, Pham Minh; Huong, Trinh Thi Thu; Grigorchuk, Valeria P.; Long, Pham Quoc; Huyen, Luu Van; Imbs, Andrey B. (Vietnam Journal of Marine Science and Technology, 2018)
In the fatty acid composition of total lipid of the soft coral Bebryce sp., the concentration of unsaturated fatty acid predominates. The composition of saturated fatty acids is very diverse, including all saturated fatty acids from C14 to C26. The unsaturated fatty acids with high concentration are C20: 4n-6, 20:5n-3, 22:6n-3, 24:5n-6, 26:3n-6, 26:2n-6, 26:2n-7, 28:3n-6. In the fatty acids composition of the studied coral, there is presence of characterized fatty acids for the existence of sponges C25-C28 (demospongic fatty acids) with total content 29,86%. Most of the Bebryce coral species do not have zooxanthellae, therefore, in the fatty acids composition, either it is lack or contains only a small amount of markers fatty acids for zooxanthellae such as 18:5n-3, 18:4n-3, 18:3n-6, 20:4n-3. In the phospholipid content of the soft coral Bebryce sp., there is presence of characterized classes for Cnidarian animals such as phosphatidylethanolamine (PE), phosphatidylchonline (PC), phosphatidylserine (PS), phosphatidylinositol (PI), phosphonolipid is ceramide aminoethylphosphonate (CAEP). PC account for the highest concentration (37,20% of total phospholipid). The molecular species of phospholipid classes of Bebryce sp. for the first time were investigated. In the results, there we 60 phospholipid molecular species identified in 5 classes. The molecular species with high content in the classes were PE 20:4/18:1e, PE 20:4/19:1, PC 20:4/18:0e, PC 20:4/16:0e, PS 24:5/18:0e, PI 24:5/18:0, CAEP18:2base/16:0 and CAEP 18:1base/16:0.